Odpowiedzi

  • Użytkownik Zadane
2010-03-14T16:39:47+01:00
A) x-3y=4
-x+6y=2
_______
3y=6
y=2

x-3*1=4
x-3=4
x=7

x=7
y=2

b) 2x-4y=6 /:2
-x+y=1

x-2y=3
-x+y=1
________
-y=4
y=-4

x-2*(-4)=3
x+8=3
x=-5

x=-5
y=-4

c) x+3y=4
x-y=0 /*(-1)

x+3y=4
-x+y=0
______
4y=4
y=1

x-1=0
x=1

x=1
y=1


d) 2x+3y=4
x+2y=3 /*(-2)

2x+3y=4
-2x-4y=-6
__________
-y=-2
y=2

x+2*2=3
x+4=3
x=-1

x=-1
y=2
Najlepsza Odpowiedź!
2010-03-14T16:43:29+01:00
A)x-3y=4
-x+6y=2
+
3y=6/:3
y=2

x-3*2=4
x-6=4
x=10

spr. 10-3*2+10-6=4

b)2x-4y=6/:2
-x+y=1

x-2y=3
-x+y=1
+
-y=4/*-1
y=-4
x-2*-4=3
x+8=3
x=-5

spr.2*-5-4*-4=-10+16=6

c)x+3y=4
x-y=0

x+3y=4
x=y

y+3y=4
x=y

4y=4/:4
x=y

y=1
x=1
spr. 1+3*1=1+3=4

d)2x+3y=4
x+2y=3/*(-2)

2x+3y=4
-2x-4y=-6
+
-y=-2/*(-1)
y=2

2x+3*2=4
2x+6=4
2x=-2
x=-1

spr. 2*(-1)+3*2=-2+6=4